Non-litigation as An Environmental Dispute Resolution Mechanism in Indonesia - Dwi Ratna Indri Hapsari; Aditya Aji Syuhadha Ilmiawan; Echaib Samira (Universitas Muhammadiyah Malang, 2022)
Environmental problems have occurred in the global scope, both developed and developing countries. Environmental problems are not only problems of developed countries or industrialized countries including Indonesia. Efforts to overcome environmental problems in developing countries have no other choice but to carry out development. Without the level of development, people will decline, and the environment will be increasingly damaged. Development must still be carried out without damaging the environment. This balance must be maintained in order to preserve the environment. Indonesia has been paying attention to environmental management since 1972. Settlement of environmental disputes through litigation does not produce many results. Dispute resolution through non-litigation channels assumes that dispute resolution through litigation results in very disappointing results. This study wants to conduct a study related to the implementation of Government Regulation No. 54 of 2000 concerning Service Providers for Environmental Dispute Resolution Services Outside the Court and find obstacles and solutions in resolving environmental disputes out of court. The implementation of Government Regulation No. 54 of 2000 at the central government level has established a service provider institution based on the Decree of the State Minister of the Environment Number 77 of 2003 concerning the Establishment of an Out-of-court Environmental Dispute Resolution Service Provider (LPJP2SLH) at the Ministry of the Environment, but its performance has not yet been felt. Abstrak Masalah lingkungan telah terjadi dalam lingkup global, regional maupun nasional baik negara maju maupun negara berkembang. Masalah lingkungan bukan hanya masalah negara maju atau negara industri namun juga pada negara berkembang termasuk Indonesia. Upaya mengatasi permasalahan lingkungan di negara berkembang tidak ada pilihan lain selain melakukan pembangunan. Pembangunan tetap harus dilakukan tanpa merusak lingkungan. Keseimbangan ini harus dijaga agar kelestarian lingkungan tetap terjaga. Indonesia telah memperhatikan pengelolaan lingkungan sejak tahun 1972. Penyelesaian sengketa lingkungan melalui litigasi tidak banyak membuahkan hasil. Penyelesaian sengketa melalui jalur non-litigasi didasarkan pada asumsi bahwa penyelesaian sengketa melalui jalur litigasi memberikan hasil yang sangat mengecewakan. Penelitian ini ingin melakukan kajian mendalam Peraturan Pemerintah Nomor 54 Tahun 2000 tentang Penyelenggara Jasa Penyelesaian Sengketa Lingkungan Hidup di Luar Pengadilan, serta mencari kendala dan solusi penyelesaian sengketa lingkungan hidup di luar pengadilan. Pelaksanaan Peraturan Pemerintah Nomor 54 Tahun 2000 di tingkat pemerintah pusat telah membentuk lembaga penyedia layanan berdasarkan Keputusan Menteri Negara Lingkungan Hidup Nomor 77 Tahun 2003 tentang Pembentukan Layanan Penyelesaian Sengketa Lingkungan Di Luar Pengadilan Penyelenggara (LPJP2SLH) di Kementerian Lingkungan Hidup, namun kinerjanya belum optimal.